JURIDICAL REVIEW OF DEFAULT IN LAND SALE AND PURCHASE AGREEMENT BASED ON THE CIVIL CODE - I Putu Adi Palguna Giri; I Made Mulyawan Subawa; I Gusti Agung Ika Laksmi Mahadewi (International Journal of Business, Law and Political Science, 2026)
Objective: Therefore, a juridical analysis is necessary to examine the legal regulation of breach of contract and the legal remedies available when a breach occurs in a land sale and purchase agreement. Method: This study uses normative legal research with a statutory approach by examining the Indonesian Civil Code, relevant legislation, court decisions, legal literature, scientific journals, and other legal materials related to agreements and breaches of contract. Results: The results of this study indicate that the legal regulation of breach of contract in land sale and purchase agreements is governed by the Indonesian Civil Code, particularly Article 1238 concerning debtor's default, Article 1243 concerning compensation for losses arising from breach of contract, Article 1320 concerning the legal requirements for a valid agreement, Article 1338 concerning the principle of freedom of contract, and Article 1457 concerning the definition of sale and purchase. In the event of a breach of contract, the aggrieved party may pursue legal remedies through non-litigation mechanisms, such as negotiation, mediation, or deliberation to reach a mutual agreement. Novelty: This study provides a juridical analysis that integrates the regulation of breach of contract with the legal remedies available to aggrieved parties in land sale and purchase agreements under the Indonesian Civil Code.